2008
DOI: 10.1007/s00436-008-1156-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of host temperature and gastric and duodenal environments on microsporidia spore germination and infectivity of intestinal epithelial cells

Abstract: Approximately 14 of the more than 1,000 species of microsporidia infect humans, only 2 of which, Enterocytozoon bieneusi and Encephalitozoon intestinalis, cause intestinal microsporidiosis. Clinical isolates of three microsporidia species, E. intestinalis, Encephalitozoon hellem, and the insect parasite, Anncaliia (Brachiola, Nosema) algerae were used in a spore germination assay, and enterocyte attachment and infection assays to model the potential roles of gastric and duodenal environments, and host temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Common cell types supporting infection have been kidney epithelial cells (Undeen 1975;Lowman et al 2000;Takvorian et al 2005); African Green monkey (Kucerova et al 2004) and fibroblasts from human lung, muscle, and foreskin (Scanlon et al 1999;Trammer et al 1999;Belkorchia et al 2008) and from Xenopus (Smith et al 1982). Also used successfully to grow A. algerae have been cells or cell lines from rat brain and skeletal muscle (Smith and Sinden 1980;Smith et al 1982;Cali et al 2004), human intestine (Leitch and Ceballos 2008), and liver (Smith et al 1982). For the warm water fish, cell lines from embryo, brain, testis, and skin became infected with A. algerae, but the skin cell line, GFSK-S1 appeared to be better at supporting the production of A. algerae life cycle stages at 6 d post-infection.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Common cell types supporting infection have been kidney epithelial cells (Undeen 1975;Lowman et al 2000;Takvorian et al 2005); African Green monkey (Kucerova et al 2004) and fibroblasts from human lung, muscle, and foreskin (Scanlon et al 1999;Trammer et al 1999;Belkorchia et al 2008) and from Xenopus (Smith et al 1982). Also used successfully to grow A. algerae have been cells or cell lines from rat brain and skeletal muscle (Smith and Sinden 1980;Smith et al 1982;Cali et al 2004), human intestine (Leitch and Ceballos 2008), and liver (Smith et al 1982). For the warm water fish, cell lines from embryo, brain, testis, and skin became infected with A. algerae, but the skin cell line, GFSK-S1 appeared to be better at supporting the production of A. algerae life cycle stages at 6 d post-infection.…”
Section: Discussionmentioning
confidence: 97%
“…For the warm water fish, cell lines from embryo, brain, testis, and skin became infected with A. algerae, but the skin cell line, GFSK-S1 appeared to be better at supporting the production of A. algerae life cycle stages at 6 d post-infection. Other hints of cell type preference were seen in the poor infection of differentiated human intestinal epithelial cells (Leitch and Ceballos 2008) and in the severe infection of the liver but not in other tissues of immunodeficient mice (Koudela et al 2001). In the future, the in vitro approach might allow the delineation of possible tissue or cell selectivity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, we found that the protein fraction of seminal fluid induced the germination of N. apis spores. Germination of microsporidia, such as Nosema, can be caused by a number of factors such as changes in pH, temperature, ionic concentrations or exposure of dehydrated spores to water [37,[40][41][42]. Regardless of the trigger, spore germination results from an increase of osmotic pressure inside the spore that eventually triggers the expulsion of the polar tube [41][42][43], but the exact mechanisms are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The infection abilities of the spores were assayed by counting the number of infected Sf9 cells based on a protocol adapted from Leitch and Ceballos (2008). Briefly, 1 Â 10 5 cell were cultured on 3.8-cm 2 transwells and maintained at 28°C in Dulbecco's modified Eagle's medium supplemented with 10 lg/ml human transferrin and 10% fetal bovine serum.…”
Section: Spore Production and Infection Assaymentioning
confidence: 99%